2020
DOI: 10.3390/rs12121946
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform-SfM and TLS Data Fusion for Monitoring Agricultural Terraces in Complex Topographic and Landcover Conditions

Abstract: Agricultural terraced landscapes, which are important historical heritage sites (e.g., UNESCO or Globally Important Agricultural Heritage Systems (GIAHS) sites) are under threat from increased soil degradation due to climate change and land abandonment. Remote sensing can assist in the assessment and monitoring of such cultural ecosystem services. However, due to the limitations imposed by rugged topography and the occurrence of vegetation, the application of a single high-resolution topography (HRT) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 124 publications
(226 reference statements)
0
35
0
Order By: Relevance
“…Many previous studies reported their effects on soil and water processes [5][6][7]. Nowadays, many artificial terraces are threatened by land degradation and soil erosion because of land abandonment and a lack of maintenance [8]. The Loess Plateau in China, which is a major agricultural production region in China, suffers from severe soil erosion and is which is a major agricultural production region in China, suffers from severe soil erosion and is a fragmented terrain [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies reported their effects on soil and water processes [5][6][7]. Nowadays, many artificial terraces are threatened by land degradation and soil erosion because of land abandonment and a lack of maintenance [8]. The Loess Plateau in China, which is a major agricultural production region in China, suffers from severe soil erosion and is which is a major agricultural production region in China, suffers from severe soil erosion and is a fragmented terrain [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the time expenditure, financial costs, and inconvenience make long-term monitoring over large areas difficult. Automatic methods are possible with the technological development of high spatial resolution remote sensing and terrain modeling by unmanned aerial vehicle (UAV) photogrammetry [16][17][18] or light detection and ranging (lidar) technology [8]. Highly accurate terrain modeling by UAV photogrammetry is consistently difficult because fully and automatically interpolating the surface model into the terrain model, i.e., the digital elevation model (DEM), is problematic in hilly areas covered with dense vegetation [19].…”
Section: Introductionmentioning
confidence: 99%
“…It's suggested that affordable and portable UAV-borne LiDAR system can generate very high resolution three-dimensional (3D) habitat information, including terrain and vegetation structure [27]. For example, Grijseels et al [28] utilized LiDAR imaging and found that the riparian vegetation structure follows the patterns of topography related to energy and water subsidies; Cucchiaro et al [29] combined the 3D photogrammetry and terrestrial LiDAR scanning (TLS) techniques and concluded that this data fusion can be utilized to create highly accurate digital terrain models (DTMs) in the context of complex and unreachable topography and vegetation cover. The high-resolution UAV and LiDAR techniques facilitate the observation practice of geomorphic change characterization [30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MVS generates a broad range of point clouds based on the predicted object position and reference point, which is used for dense reconstruction. This technology has been extended to land surface changes [ 16 , 17 ], river erosion [ 18 ], and rock failure [ 19 ], among others. Some works even achieve a highly accurate reconstruction model that indicates SfM-MVS could provide a survey precision comparable to the current measurement methods [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%